Interferensi Bahasa Daerah Manggarai terhadap Penggunaan Bahasa Indonesia pada Mahasiswa FKIP Prodi Pendidikan Bahasa Indonesia Universitas Pancasakti Makassar : Manggarai Regional Language Interference on Indonesian Language Use among Students FKIP, Indonesian Language Education Study Program Pancasakti University Makassar - Fenilia Anul; Nuzul Tenriana; Andi Muhammad Nur; Rusman Latif; Imran Imran (Universitas Tidar, 2025)
Regional language interference remains a common issue in the use of Indonesian in higher education, particularly among students who are native speakers of the Manggarai language. This phenomenon appears through the influence of regional linguistic structures and vocabulary on the accuracy of Indonesian sentences. This study aims to identify the forms of Manggarai language interference in the Indonesian used by students of the Indonesian Language Education Study Program, FKIP, Universitas Pancasakti Makassar, and to describe its manifestations in interrogative, exclamatory, and conditional sentences. This research employs a descriptive qualitative approach, with data consisting of utterances obtained from interviews and recorded conversations with students. Data were collected through interviews and participant observation, and analyzed using the Miles and Huberman model. The findings show that interference is most frequently found in interrogative sentences, amounting to 14 out of 23 data (60.87%). Interference in exclamatory sentences appears in 5 data (21.74%), while conditional sentence interference is the least, with 4 data (17.39%). These results indicate that interrogative sentence structures are the most vulnerable to the influence of the Manggarai language. Therefore, greater reinforcement is needed to encourage the consistent use of standard Indonesian, particularly in constructing interrogative sentences.